The trade effects of the economic partnership agreements between the European Union and the African, Caribbean and Pacific group of states: Early empirical insights from panel data - Frederik Stender; Axel Berger; Clara Brandi; Jakob Schwab (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
This study provides early ex-post empirical evidence on the effects of provisionally applied Economic Partnership Agreements (EPAs) on two-way trade flows between the European Union (EU) and the African, Caribbean and Pacific Group of States (ACP). Employing the gravity model of trade, we do not find a general EPA effect on total exports from ACP countries to the EU nor on total exports from the EU to ACP countries. We do, however, find heterogeneous effects when focusing on specific agreements and economic sectors. While the agreement between the EU and the Caribbean Forum (CARIFORUM), which concluded several years ahead of the other EPAs in 2008, if anything, reduced imports from the EU overall, the provisional application of the other EPAs seems to have at least partly led to increased imports from the EU to some partner countries. More specifically, the estimation results suggest an increase in the total imports from the EU only in the Southern Africa Development Community (SADC) EPA partner countries. On the sectoral level, by comparison, we find increases in the EU's agricultural exports to SADC, Eastern and Southern Africa (ESA) and the Pacific. Lastly, in the area of manufactures trade, we find decreases of exports of the ESA and SADC countries to the EU, but increases in imports from the EU into SADC countries. While this early assessment of the EPA effects merits attention given the importance of monitoring future implications of these agreements, it is still too early for a final verdict on the EPAs' effects and future research is needed to investigate the mid- and long-term consequences of these agreements.
Keywords: 330